Synthesis and biological evaluation of truncated derivatives of abyssomicin C as antibacterial agents - Monjas, Leticia; Fodran, Peter; Kollback, Johanna; Cassani, Carlo; Olsson, Thomas; Genheden, Maja; Larsson, D. G. Joakim; Wallentin, Carl-Johan (Beilstein Journal of Organic Chemistry, 2019)
The synthesis and antibacterial activity of two new highly truncated derivatives of the natural product abyssomicin C are reported. This work outlines the limits of structural truncation of the natural product and consequently provides insights for further structure–activity relationship studies towards novel antibiotics targeting 4-amino-4-deoxychorismate (ADC) synthase. Specifically, it is demonstrated that the synthetically challenging bicyclic motif is essential for activity towards methicillin-resistant Staphylococcus aureus (MRSA).
Keywords: abyssomicin C; antibiotic; antibiotic resistance; MRSA; truncated natural products